Multiprogram Interaction between Mitigation and Adaptation Programs: Optimization Opportunity for Governments Addressing Climate Change - Lilford, Eric; Maybee, Bryan; Packey, Daniel (2019)
This article addresses the concepts of economies of scope and multiprogram production, subadditivity and transray convexity as it applies to program optimization. The article goes on to expand these concepts to include the special case of climate change. As mitigation and adaptation programs addressing climate change are considered public goods and thus fall under the purview of governments, it discusses how the modification of climate change programs can develop a relationship across the cost functions of the modified mitigation and adaptation program production and consequently how this interrelationship affects the net benefit maximizing conditions.